2020
DOI: 10.1101/2020.11.18.20234369
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Antibodies to SARS-CoV-2 are associated with protection against reinfection

Abstract: BackgroundIt is critical to understand whether infection with Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) protects from subsequent reinfection.MethodsWe investigated the incidence of SARS-CoV-2 PCR-positive results in seropositive and seronegative healthcare workers (HCWs) attending asymptomatic and symptomatic staff testing at Oxford University Hospitals, UK. Baseline antibody status was determined using anti-spike and/or anti-nucleocapsid IgG assays and staff followed for up to 30 weeks. We … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
70
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(78 citation statements)
references
References 27 publications
4
70
0
4
Order By: Relevance
“…Given the possible reduction in nAb titre over time the protection they provide could be limited. However, more recent evidence from a large cohort of UK health professionals has shown anti-S IgG generated following natural infection may protect from re-infection up to six months [173], consistent with emerging data on the durability of neutralising antibodies. Further evidence on longer durability and correlates is required.…”
Section: Plos Onesupporting
confidence: 71%
“…Given the possible reduction in nAb titre over time the protection they provide could be limited. However, more recent evidence from a large cohort of UK health professionals has shown anti-S IgG generated following natural infection may protect from re-infection up to six months [173], consistent with emerging data on the durability of neutralising antibodies. Further evidence on longer durability and correlates is required.…”
Section: Plos Onesupporting
confidence: 71%
“… 8 Recent unpublished studies in HCWs reported no evidence of symptomatic reinfection, suggesting that immunity is maintained for at least 6 months. 9 , 10 In these studies there was a relatively low event rate (123 and 20 symptomatic infections respectively). It is possible that the protective immunity observed may have been explained in part by the relatively low incidence of SARS-CoV-2 infection.…”
mentioning
confidence: 88%
“…Individuals who are infected with SARS-CoV-2 develop both cellular and humoral immune responses to the virus ( Robbiani et al, 2020 ; Gaebler et al, 2020 Preprint ; Suthar et al, 2020 ; Ni et al, 2020 ; Grifoni et al, 2020 ; Peng et al, 2020 ; Sekine et al, 2020 ; Rydyznski Moderbacher et al, 2020 ; Braun et al, 2020 ; Zhou et al, 2020 ). Antibody responses develop to most of the structural proteins expressed by the virus, and nearly all individuals develop neutralizing antibodies directed to the receptor binding domain of the Spike trimer (S; Robbiani et al, 2020 ; Gaebler et al, 2020 Preprint ; Suthar et al, 2020 ; Ni et al, 2020 ; Lumley et al, 2020 Preprint ). Cellular immune responses can be broad but vary widely ( Grifoni et al, 2020 ; Peng et al, 2020 ; Sekine et al, 2020 ; Rydyznski Moderbacher et al, 2020 ; Braun et al, 2020 ; Zhou et al, 2020 ), and lymphopenia is a prominent feature of more severe infection, affecting CD4 + and CD8 + T cells, as well as B cells ( Tavakolpour et al, 2020 ; Chen and John Wherry, 2020 ; Huang et al, 2020 ; Giamarellos-Bourboulis et al, 2020 ; Tan et al, 2020 ; Kuri-Cervantes et al, 2020 ; Mathew et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%